Nutritive Value of Some Concentrate Feedstuffs for Guinea Pigs (Cavia porcellus) - Gilbert Alagón; Gardenia Tupayachi; Wagner Villacorta; Carla Taco; Moises Jancco; Eloy Zuniga; María del Carmen López-Luján; Luis Ródenas; Vicente Javier Moya; Eugenio Martínez-Paredes; Enrique Blas; Juan José Pascual (Animals)
The objective of this work was to ascertain the nutritive value of six concentrate feedstuffs commonly used in guinea pig feed manufacturing through the substitution method. Six test diets were obtained by replacing the corresponding basal mixture with 40% corn, 50% barley, 45% wheat bran, 35% soybean meal, 30% pigeon pea, or 30% Leucaena leaf meal. Sixty-three guinea pigs were randomly assigned to one of the nine experimental diets (three basal diets and six test diets, with seven animals per diet). The animals were housed in individual cages and provided with feed and water ad libitum. Following a ten-day adaptation period, the feed intake and faeces excretion were monitored for a further five days. The digestible energy content, expressed as kcal/kg dry matter (±standard error), was 3857 ± 83 for corn, 3454 ± 68 for barley, 2911 ± 110 for wheat bran, 3855 ± 81 for soybean meal, 3105 ± 79 for pigeon pea, and 2972 ± 72 for Leucaena leaf meal. The apparent total tract digestibility of crude protein, expressed as % (±standard error) was 73.8 ± 4.9 for corn, 69.5 ± 4.6 for barley, 76.4 ± 3.6 for wheat bran, 88.4 ± 1.0 for soybean meal, 62.1 ± 1.9 for pigeon pea, and 68.0 ± 1.8 for Leucaena leaf meal. Further research is required to increase knowledge about these and other feedstuffs for guinea pigs.